The Influence of the Carousel Feedback Learning Model on Higher Order Thinking Skills (HOTS) - Guntur Gunawan; Rohania; Yuyun Yumiarty (UNIB Press, 2024)
Teachers have not used the student-enhancing learning model (HOTS) in the teaching and learning process. This can be seen from the learning outcomes which are still below average. Research purposes; 1) knowing the students' initial abilities; 2) knowing the difference in average values; 3) determine the effect of the Carousel Feedback learning model on HOTS in class V science learning at SDN 13 Rejang Lebong. This research is experimental research, with a true experimental research design. Data collection techniques include observation, tests and documentation, as well as data analysis techniques in the form of normality, homogeneity and Independent Sample t-test. The research results show; 1) The initial ability of the experimental class was 49.57, while the control class was 50.95. it was concluded that the average pre-test score for the experimental class and control class was below the average <65; 2) a significant difference in the average post-test results for the experimental class was 86.22 and the average post-test results for the control class was 75.86. ; 3) There is an influence of using the Carousel Feedback learning model on class V students at SDN 13 Rejang Lebong. This can be seen from the results of the Independent Sample t-Test analysis, namely the value of tcount = 5.893 ≥ ttable = 1.681 with a significance level of α= 0.05. It can be concluded that the Ha hypothesis is accepted and H0 is rejected.